The Management of the Weather Risk on the Electric Energy Market - Wlodarczyk, A.; Zawada, M. (Электронное моделирование, 2009)
The aim of this study is to present a new approach for analyzing the effect of temperatures, wind speed and heating degree days index on the variability of the daily demand for electric energy in Silesian region. Specific nature of the time series used in this paper concerning the electric energy consumption and the weather variables, such as temperature or heating degree day index, requires application of a special class of models —ARFIMAX—GARCH (Generalized Autoregressive Conditional Heteroscedastic model). Рассмотрен новый подход к анализу влияния температуры, скорости ветра и индекса степени дневного нагрева на изменчивость суточного потребления электроэнергии в районе Силезии. Особенности используемых временных рядов связаны с потреблением электроэнергии и погодными переменными, такими как температура или индекс степени дневного нагрева, обусловливают применение специального класса моделей — ARFIMAX—GARCH (обобщенная авторегрессионная условная гетероскедастическая модель). Розглянуто новий підхід до аналізу впливу температури, швидкості вітру та індексу ступеню денного нагріву на змінність добової потреби в електроенергії в районі Сілезії. Властивості використаних часових рядів, пов’язані з споживанням електроенергії та погодними змінними, такими як температура чи індекс ступеню денного нагріву, обумовлюють застосування спеціального класу моделей — ARFIMAX—GARCH (узагальнена авторегресійна умовна гетероскедастична модель).